Treasure - Williamson, Chris; Gordon, Ansley; Mercurio, Matt; Hardy, John; Sunfire Films (Firm); Leomark Studios ([Orlando, Florida] : Sunfire Films, 2017)
Popular party girl Erica gets a dose of reality when she's forced to do community service at a soup kitchen. Still reeling from losing her mother to cancer, she is aloof and distant from her father Ethan when she gets into a car accident and is placed at Angela's Soup Kitchen by her case worker Ramona. She hates it, believing she is being unfairly punished. But a new friendship based on a mutual love for geo-caching and the realization that the patrons of the soup kitchen are much worse off than she could've imagined leads Erica to ask herself what is the meaning of life, and where can she find it? --
Originally released as a motion picture in 2017.
Ansley Gordon, Matt Mercurio, John Hardy, Rebecca Blair, Shanise Jordan, Liz Day.
Cinematographer, Mike Collins ; editor, Jordan Chipps ; music, Andrew Scott Foust.
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 30, 2020)
Keywords: Geocaching (Game) -- Drama; Friendship -- Drama; Self-actualization (Psychology) -- Drama; Families -- Drama; Fiction films; Feature films; Internet videos; Streaming video